Mieloma múltiplo em uma cadela de 10 anos - Gurgel, Natália Peixoto Carioca; Cabral, Leonardo Alves Rodrigues; dos Santos, Maressa Holnada; Rocha, Danilo Galvão; de Almeida, Talles Monte; Costa, Paula Priscila Correia (Acta Scientiae Veterinariae, 2017)
Background: The malignant neoplasms, in general, constitute one of the main causes of death in dogs and cats. The multiple myeloma is a neoplasm characterized by the monoclonal proliferation of plasma cells in the bone marrow, causing several systemic symptoms and it is rare in pets, representing less than 1% of the malignant neoplasms in these animals. It usually occurs in older dogs. Thus, the purpose of this report was to describe a case of multiple myeloma in a 10-year-old poodle dog, occurred in the Veterinary Hospital Unit of the State University of Ceará. Case: A 10-year-old Poodle bitch was admitted in the Veterinary Hospital Unit of the State University of Ceará presenting lump erythematosus, alopecic, soft and ulcers in the region of the digits of the left front leg, pain and lameness. The blood count evidenced normocytic and normochromic anemia, presence of rouleaux, lymphopenia and monocytopenia, and the biochemical exams have demonstrated an elevated value of alanine aminotransferase (ALT). The cytology of the nodule indicated probable diagnosis of plasma cell neoplasm and radiographic examination showed the presence of bone lysis, and therefore the patient underwent amputation of the affected limb surgery. A biopsy of the nodule indicated neoplastic proliferation, with an arrange compatible to plasmacytoma of cleaved type. A follow-up consultation was realized 30 days after surgery, and 2 new nodules appeared in the superior lip region and close to the surgery site. A new blood count indicated anemia with presence of rouleaux, thrombocytopenia, leucopenia, lymphopenia and monocytopenia, and the biochemical results showed a discrete diminution of aspartate aminotransferase(AST) and a considerable increase on the alkaline phosphatase levels. The cytology of the new nodules indicated plasmacytoma, and was realized a myelogram, that showed dysplastic marrow plasma cells, with more than 20% of plasma cells. Discussion: In the present case, the patient’s lump grew rapidly with bleeding and ulcer formation. The animal presented bone involvement, which characterizes the most suggestive sign of multiple myeloma. Justified by the stimulating factor of osteoclasts, promoting bone lysis, which can cause pathological fractures and pain. The amputation was a partial treatment to attenuates the discomfort and pain presented by the patient. The appearance of new nodules stimulated a more detailed investigation for multiple myeloma. The enzyme AST presented a discrete diminution, and ALT initially was higher than normal, but then returned to normal values. So, the elevated activity of alkaline phosphatase directed the suspects to multiple myeloma, since the activity of AST and ALT was normal, the alkaline phosphatase level was ligated to bone diseases. The rouleaux was constant at the hemograms, this is justified by the excess of immunoglobulins produced in marrow. Based on the chart presented by the patient, the bone marrow was punctured for myelogram. The symptoms displayed by the animal along with the cytological analysis, histopathological, hematological, biochemical and with myelogram indicated diagnosis of multiple myeloma. Other exams could be investigated, for example, detection of Bence Jones proteinuria, serum calcium dosage and inmunoelectroforesis for determination of the type of immunoglobulin produced by the plasma cells in the bone marrow. The definitive diagnostic was established approximately three months after the first consult, emphasizing the importance of a multiple myeloma differential diagnostic in case of plasma cell neoplasm.